ESTIMATION OF SUPPLY RESPONSE OF FISH IN BORNO STATE, NIGERIA - YaAshe, M Bulama; Abba , A Makinta; Usman, A Buba (Economics and Statistics Research Journal (ESRJ), 2025)
Fish is one of the richest animal proteins that is commonly consumed by both rich and people whose incomes are below the federal poverty threshold in Nigeria. The supply response of fish in Borno State, Nigeria was estimated. The study specifically analyzed the trend of quantity supplied of fish and estimated the responsiveness of fish supply to changes in price and non-price factors in Borno State. Time series data spanning January 2017 to December 2022 were obtained from the National Bureau of Statistics (NBS) and Food and Agriculture Organization Statistics (FAOSTAT). The data were subjected to a unit root test and analyzed using graphs and a vector error correction. The results indicated that there were fluctuations in the quantity of fish supplied overtime. The study also revealed the short and the long run relationships between the quantity of fish supplied and the prices of fish and its substitutes: dried tilapia, iced sardine, fresh tilapia, fresh African Arowana (Bargi), smoked catfish, fresh catfish, beef and chicken. Fish supply was revealed to be responsive to changes in price and non-price factors. It is recommended that fish farmers, processors, and marketers closely monitor changes in fish prices and substitute prices, and adjust their production and marketing strategies accordingly to, maximize their benefits and remain competitive in the market